National Histories, International Genre: Thackeray, Balzac, and the Franco-British Bildungsroman - Cole, Sarah (Romanticism and Victorianism on the Net, 2007)
AbstractThe Bildungsroman genre poses a productive challenge for the study of Victorian internationalisms. On the one hand, scholars of German literature often contend that the genre is inextricably tied to German concepts of culture and nationhood; on the other hand, half a century of scholarly practice has linked the term “Bildungsroman” to novels of personal education across Europe and beyond. Seeking to interrogate, rather than simply assume, the internationalism of the Bildungsroman genre, I focus on the Franco-British literary exchanges inscribed in a major Victorian Bildungsroman, William Makepeace Thackeray’s Pendennis. Drawing on a variety of theoretical and historical models, including Margaret Cohen and Carolyn Dever’s concept of the “Channel zone,” I suggest that Pendennis forms a point of intersection between the British and French national traditions of the Bildungsroman, thus allowing us to see how a genre with a German name was modified in its passage between France and Britain. Although Thackeray is often thought of as an apolitical writer—a satirist concerned only with the manners and morals of the middle and upper classes—I argue that Pendennis was crucially shaped by his engagement with the French Revolution of 1848. In order to face and exorcise the threat of revolution, I further suggest, Thackeray turned to the French Bildungsroman tradition; my hypothesis is that Thackeray reworked Balzac’s Lost Illusions, transforming Balzac’s narrative of revolutionary dislocation into a self-consciously British narrative of peaceful change. By working both with and against French literary models, Thackeray reveals the formation of British identity as a complex process of cross-Channel negotiation, rather than a simple negation of the French “other.”